Herbal NF-κB Inhibitors Sensitize Rituximab-Resistant B Lymphoma Cells to Complement-Mediated Cytolysis - Ge, Xiaowen; Du, Yiqun; Chen, Jianfeng; Zhu, Na; Yao, Jiamei; Zhang, Xin; Wang, Na; Sun, Yujing; Gao, Feng; Hu, Weiguo; Hou, Yingyong (Frontiers in Oncology, 2021)
Background: Drug resistance remains a serious challenge to rituximab therapy in B-NHL (B cell non-Hodgkin’s lymphoma). CDC (complement-dependent cytotoxicity) has been proposed as a major antitumor mechanism of rituximab, and direct abrogation of CD59 function partially restores rituximab sensitivity with high efficacy. However, universal blockade of CD59 may have deleterious effects on normal cells. Sp1 regulates constitutive CD59 expression, whereas NF-κB and CREB regulate inducible CD59 expression. Methods: Immunohistochemistry (IHC) assay was used to detect the expression levels of CD59 and other related molecules. Quantitative Real-time PCR (RT-PCR) analysis was used to explore the levels of transcripts in original and resistant cells. We chose LY8 cells to test the effects of NF-κB and CBP/p300 inhibition on CD59 expression using flow cytometry (FACS). Immunoblotting analysis was employed to detect the effects of curcumin and POH. The in vitro and in vivo experiments were used to evaluate the toxicity and combined inhibitory effect on tumor cells of curcumin and POH. Results: We demonstrated that herbal (curcumin and perillyl alcohol) blockade of NF-κB specifically suppresses the expression of inducible CD59 but not CD20, thus sensitizing resistant cells to rituximab-mediated CDC. Moreover, activation of NF-κB and CREB is highly correlated with CD59 expression in B-NHL tissues. Conclusions: Our findings suggest the potential of CD59 expression as a predictor of therapeutic efficacy of NF-κB inhibitors in clinical application as well as the rationality of a NF-κB inhibitor-rituximab regimen in B-NHL therapy.